When do consumers value ethical attributes? The role of perceived quality in gift-giving - Das, Gopal; Peloza, John; Varshneya, Geetika; Green, Todd (European journal of marketing, 2021)
Purpose Although research demonstrates the importance of ethical product attributes for consumers, a prior study has not examined the role of consumption target (i.e. self-purchases vs gift-giving) on consumers’ preference for products with ethical attributes. Notably, consumers’ preference for quality can differ between self-purchases and gifts, and the presence of ethical attributes can impact product quality perceptions. The purpose of this paper is to examine how the presence of ethical attributes alters decision-making in a gift-giving context using perceptions of product quality as an explanatory variable for these differences. Design/methodology/approach One field study and two controlled experiments test the proposed hypotheses. The experiments were conducted across different product categories and samples. Findings Results showed that the presence of an ethical attribute leads to higher purchase intentions for products in a gift-giving context compared to self-purchase. Perceived quality mediates this effect. Further process evidence through moderation, including resource synergy beliefs, support the findings. This paper discusses the theoretical, managerial and societal implications of these results. Research limitations/implications Although care was taken to select products to enhance generalizability, the studies presented here are limited to two products. Further, although the present research includes a field study with actual charity-related purchases, the role of time pressures is not explicitly explored. Finally, the role of brand-self connections is not explored in the current research. The ability for a donor to integrate the mission of a charity into their self-perception or the potential for social normative influences to impact behaviors remains open for exploration. Practical implications Charities are facing increasing pressures to raise sustainable funds to support their missions. The research provides guidance to marketers and fundraisers in the non-profit sector that allows them to direct more focused fundraising appeals to donors and adapt their fundraising efforts to create a fit between their audience and fundraising appeals. Originality/value This research demonstrates that consumption target (purchasing for the self versus purchasing for others) is a vital contextual factor that influences customer preference for ethical attributes. These results complement the extant literature by exploring the underlying mechanism behind consumers’ responses to the ethical attributes in the case of self-purchase and other-purchase. The underlying effect is supported theoretically by resource synergy beliefs.